La industria forestal del Estado de Chihuahua - Ruelas Monjardín, Laura C.; Dávalos Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
This paper offers an outlook of the forest industry of Chihuahua, taking into account its development over the last three decades; for this purpose it is considered, for comparative ends, its strongest competitor, that of Durango state, and the place that both occupy in the national context. Statistical data are presented in regards to  the forest surface and the data on  wood stocks.The state forest production has being experiencing yearly decrements. With respect to the national context, the farming and animal husbandry, forestry and fishery sector of Chihuahua has an outstanding support of  the Gross Domestic Product (GDP). This presence is stronger if it is considered  that the wood and wood based industry provided 15% of the GDP of the manufacturer industry. In terms of the number of established industries, in the last decade, this number keeps stable.The main problems that the state forestry industry face are presented, along with some measures that the goverment and the private sector are taking in order to offset the negative impact of the commercial globalization and the technological lag that this sector currently show.